2021
DOI: 10.17352/aaa.000010
|View full text |Cite
|
Sign up to set email alerts
|

A combination treatment of IFN-α2b and IFN-γ accelerates viral clearance and control inflammatory response in COVID-19: Preliminary results of a randomized controlled trial

Abstract: Early studies with combination treatments of a type I IFN and IFN- revealed synergistic inhibition of SARS CoV replication in vitro [9][10][11][12]. IFN- is a critical regulator linking the innate and adaptive immune responses [13] Moreover, combination treatments with antivirals that target different stages of the virus replicative cycle [14-16] and IFN-2b and IFN- may synergize further to accelerate viral clearance. Accordingly, we conducted a phase II randomized clinical trial to evaluate whether a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Our sample size is small, and the timing of Viral dissemination is determinant in the establishment of severe disease [44]. Therefore, the shortening of time to virus clearance as has been demonstrated by Idelis, et al for HeberFERON [32] and the results from this study, will impact favorable in the disease outcome in COVID-19 infected patients, even in the era of vaccines. Depletion of antiviral defenses related to immune response [45] and insuffi cient activation of the IFN system [46] are key points of innate immune failure to control viral persistence.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Our sample size is small, and the timing of Viral dissemination is determinant in the establishment of severe disease [44]. Therefore, the shortening of time to virus clearance as has been demonstrated by Idelis, et al for HeberFERON [32] and the results from this study, will impact favorable in the disease outcome in COVID-19 infected patients, even in the era of vaccines. Depletion of antiviral defenses related to immune response [45] and insuffi cient activation of the IFN system [46] are key points of innate immune failure to control viral persistence.…”
Section: Discussionmentioning
confidence: 65%
“…It was found that after 5 days of therapy 25% of patients had clear the virus from oral swabs [40]. Recently, Idelsi EM, et al [32] found that with the use of HeberFERON the time to reach the negativization of the SARS-CoV-2 measured by RT-PCR was 3 days in a 50% of a cohort SARS-CoV-2 asymptomatic or mild to moderate symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations